Non-hematopoietic erythropoietin-derived peptides for atheroprotection and treatment of cardiovascular diseases - Veronika S. Belyaeva; Yulia V. Stepenko; Igor I. Lyubimov; Alexandr L. Kulikov; Alesia A. Tietze; Indira S. Kochkarova; Olga V. Martynova; Olga N. Pokopeyko; Liliya A. Krupen'kina; Andrey S. Nagikh; Vladimir M. Pokrovskiy; Evgeniy A. Patrakhanov; et al. (Belgorod National Research University, 2020)
Relevance: Cardiovascular diseases continue to be the leading cause of premature adult death. Lipid profile and atherogenesis: Dislipidaemia leads to subsequent lipid accumulation and migration of immunocompetent cells into the vessel intima. Macrophages accumulate cholesterol forming foam cells - the morphological substrate of atherosclerosis in its initial stage. Inflammation and atherogenesis: Pro-inflammatory factors provoke oxidative stress, vascular wall damage and foam cells formation. Endothelial and mitochondrial dysfunction in the development of atherosclerosis: Endothelial mitochondria are some of the organelles most sensitive to oxidative stress. Damaged mitochondria produce excess superoxide and H2O2, which are the main factors of intracellular damage, further increasing endothelial dysfunction. Short non-hematopoietic erythropoietin-based peptides as innovative atheroprotectors: Research in recent decades has shown that erythropoietin has a high cytoprotective activity, which is mainly associated with exposure to the mitochondrial link and has been confirmed in various experimental models. There is also a short-chain derivative, the 11-amino acid pyroglutamate helix B surface peptide (PHBSP), which selectively binds to the erythropoietin heterodymic receptor and reproduces its cytoprotective properties. This indicates the promising use of short-chain derivatives of erythropoietin for the treatment and prevention of atherosclerotic vascular injury. In the future, it is planned to study the PHBSP derivatives, the modification of which consists in adding RGD and PGP tripeptides with antiaggregant properties to the original 11-member peptide.